PEMBERIAN PELATIHAN TERHADAP PAR PELAKU UMKM DALAM PROSES PEMBUATAN EMPING DI DESA BAYUMUNDU KECAMATAN KADUHEJO KABUPATEN PANDEGLANG-BANTEN - Asep Munir Hidayat; Saepudin Saepudin; Nadya Zulfa Salsabila; Pusparandini Raksadewi (Indonesian Collaboration Journal of Community Services, 2021)
One of the obligations as a lecturer in carrying out the tridharma is through community service. This community service has the aim of increasing the capabilities and skills of business actors in making chips and strives to be able to immediately switch from conventional to modern industry. Based on our analysis as a community service team, this community service is held from August 9 to August 14, 2021, taking approximately 45 (forty five) days, and is located at the Bayumundu village hall, Kaduhejo District, Pandeglang Regency, Banten. The number of participants is approximately 20 (twenty) participants, 70% are business people and some are local residents. The first day of training as: product variant training, the third day of product packaging training, and the fifth day of training on bookkeeping and making simple financial reports. The methods applied in these trainings are through lectures or material presentations, demonstrations, practical exercises and discussions with the participants. After the training activities are completed, a survey and evaluation will be carried out by the training committee, to see how much impact the changes have on the SMEs making the chips. The results of the training show that the trainings in this community service program are very effective and on target. This is all evidenced by the results of a survey a week after the training, it turns out that many participants immediately put it into practice. Through this training, various skills are expected to be able to provide encouragement in increasing skills including being able to make proposals, product variants, product packaging, product marketing using social media, business bookkeeping, and making simple financial reports for MSME actors. Making chips in the village of Bayumundu, District Kaduhejo, Pandeglang Regency, Banten. These trainings are also expected to be able to increase the income of business actors, so that they can prosper all parties, especially business actors and employees, and have a positive impact on growing local government income which will have an impact on equitable regional development.  All the obstacles that arise in each training can be overcome through two-way communication, and mutually build each other, so that event after event can run well according to this plan all thanks to the cooperation of all parties. As for the criticisms and suggestions that can be submitted from the results of the community service program, the participants are expected to continue to have enthusiasm and motivation in developing their business through the trainings that have been provided. Academics can always transfer knowledge to all parties who need it